The task planner : an intervention resource for human service professionals - Reid, William James, 1928- (Columbia University Press, 2000)
A comprehensive, A-to-Z set of task planners for more than one hundred psychosocial problems from alcoholism and anxiety to domestic violence and sexual abuse. Each entry includes a menu of actions the client can undertake to affect resolution, a guide to the practitioner's role in facilitating these actions, and a reference list. An accompanying disk allows social workers to update the task planners they are working with and enables keyword searches for specific topics.